Analisis Pemenuhan Kapabilitas Aparat Pengawasan Intern Pemerintah Level 3 pada Inspektorat Provinsi Kepulauan Bangka Belitung - Susanto, Andhika Putra; Hidajat, Sjarief (Universitas Pendidikan Ganesha, 2022)
This study aims to identify the capabilities of the Government Internal Supervisory Apparatus (APIP) in Inspectorate of Bangka Belitung Island Province based on the Internal Audit Capability Model (IA-CM). This research uses a qualitative research referring to IA-CM framework for assessment of internal audit capability in Inspectorate of Bangka Belitung Island Province. The research data collection method uses document review, literature review, and interview. The focus of this research is the capability of APIP carried out on each KPA in each Element (Element 1 to Element 6) which is in Level 2 (Infrastructure) and Level 3 (Integrated) by using IA-CM. The results of this study indicate that the capability level of APIP in Inspectorate of Bangka Belitung Island Province is currently at level 3 (integrated). In each element, all relevant audit policies, processes and procedures are defined, implemented and integrated.Â Â